NORMATIVE ANALYSIS OF LEGAL PROTECTION FOR FOOTBALL SUPPORTERS AT ATLETIK 17 DECEMBER STADIUM IN MATARAM CITY - I Komang Tresna; Emirald Isfihan; Rahayu Sri Utami (JILPR Journal Indonesia Law and Policy Review, 2026)
Football, as a highly popular sport, involves the attendance of thousands of supporters who may potentially face various risks related to security, comfort, and the fulfillment of their rights as consumers. Although consumer rights are regulated under Law Number 8 of 1999 on Consumer Protection, their implementation in practice remains suboptimal, particularly with regard to the responsibility of match organizers toward supporters who suffer losses at Atletik 17 December Stadium in Mataram City. This study aims to analyze the legal protection afforded to football supporters under the Consumer Protection Law, as well as the obligations of match organizers toward supporters at Atletik 17 December Stadium. This research employs a normative legal research method with a library-based approach, utilizing primary and secondary legal materials collected through both online and offline literature studies and analyzed qualitatively. The findings indicate that significant issues persist in the provision of consumer protection for football supporters, particularly concerning aspects of security, comfort, safety, and complaint-handling mechanisms. These issues are influenced by the low level of awareness among match organizers regarding their legal obligations, weak supervision by the relevant authorities, and the lack of active participation by supporters in asserting their rights. As a result, the overall comfort and sense of security experienced by supporters while attending matches at Mangemaci Stadium remain inadequate. Therefore, strengthening consumer protection is necessary to ensure the safe and comfortable organization of football matches and to foster a harmonious relationship among supporters, match organizers, and stadium management.